Current Trends in Analysis and Its Applications - Mityushev, Vladimir (Springer, 2015)
This book is a collection of papers from the 9th International ISAAC Congress held in 2013 in Kraków, Poland. The papers are devoted to recent results in mathematics, focused on analysis and a wide range of its applications. These include up-to-date findings of the following topics.